Evolução da coleta seletiva solidária efetivada pelo Banco do Nordeste do Brasil S.A. e seus impactos ambientais, sociais e econômicos no cotidiano dos participes - Dias, Ricardo Hélio Holanda (2024)
One of the major concerns in the contemporary socio-environmental landscape focuses on understanding sustainability and its various ways of implementation, seeking the maintenance of natural resources and the continuation of human existence in harmony with biomes. In this context of searching for sustainability, it becomes necessary to investigate Solidarity Selective Collection as a tool aimed primarily at building a culture based on new paradigms in the management of waste produced by institutions. This research aims to present an investigation into the waste management process of solid waste produced by the Banco do Nordeste do Brasil in recent years, also aiming to analyze the positive environmental impacts that such practices can achieve. The methodology adopted in the construction process of the study can be defined as exploratory research, whose analysis material is a bibliographic investigation, in official documents produced and made available by the Banco do Nordeste do Brasil. At the end of the research, it is concluded that the practices adopted by the Bank are of great relevance in the process of building sustainable actions, in addition to presenting considerable social impacts, since it collaborates directly with the reality of the Collectors Network in the State of Ceará.